2020
DOI: 10.1002/jgm.3136
|View full text |Cite
|
Sign up to set email alerts
|

Interplay between the RNA binding‐protein Musashi and developmental signaling pathways

Abstract: Musashi comprises an evolutionarily conserved family of RNA-binding proteins (RBP) that regulate cell fate decisions during embryonic development and play key roles in the maintenance of self-renewal and differentiation of stem cells and adult tissues.More recently, several studies have shown that any dysregulation of MSI1 and MSI2can lead to cellular dysfunctions promoting tissue instability and tumorigenesis.Moreover, several reports have characterized many molecular interactions between members of the Musas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
21
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 18 publications
(21 citation statements)
references
References 117 publications
0
21
0
Order By: Relevance
“…These characteristics demand urgent identification of predictive biomarkers of prognosis to guide and improve clinical management 5 . Given that aberrant expression of RBPs has been implicated in cancer development, and because RBPs have been recognized as biomarkers of prognosis and potential therapeutic targets, here we explored the role of MSI2 expression and its clinical implications in ACC pathobiology 7,8 …”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…These characteristics demand urgent identification of predictive biomarkers of prognosis to guide and improve clinical management 5 . Given that aberrant expression of RBPs has been implicated in cancer development, and because RBPs have been recognized as biomarkers of prognosis and potential therapeutic targets, here we explored the role of MSI2 expression and its clinical implications in ACC pathobiology 7,8 …”
Section: Discussionmentioning
confidence: 99%
“…Recently, several studies have shown that dysregulated expression and activity of RNA‐binding proteins (RBPs) as posttranscriptional regulators are associated with initiation, progression, and chemoresistance of various types of tumors 6–8 . The RBP Musashi‐2 (MSI2) has recently been recognized as a potential prognostic biomarker or a therapeutic target, or both, in many cancers, including hematopoietic malignancies and solid tumors 6,8 . Elevated expression of MSI2 plays important roles in malignant transformation, tumor proliferation, cell cycle, migration, invasion, epithelial‐mesenchymal transition (EMT), and autophagy 9–16 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the intestinal epithelium, a requirement for vertebrate Msi proteins in maintaining quiescent intestinal stem cells has been demonstrated (Yousefi et al, 2016). Interestingly, vertebrate Musashi proteins have been shown to interact with the Notch, Transforming Growth Factor Beta (TGF-ß), Wnt and Hh signalling pathways in differing contexts (reviewed in (das Chagas, Baroni, Brassesco, & Tone, 2020)). Here we describe a specific context where Drosophila Msi is required for epithelial stem cell homeostasis and demonstrate an interaction between Msi and the Wnt signalling pathway.…”
Section: Discussionmentioning
confidence: 99%
“…In the absence of murine msi1 , the differentiation potential of neuronal precursors is lost (Sakakibara et al, 2002 ). In vitro studies showed that during cell differentiation, Msi1 modulates the Notch pathway by binding to the 3′UTR of numb mRNA, which results in inhibition of numb mRNA translation and thereby an increase in Notch signaling (Imai et al, 2001 ; Berdnik et al, 2002 ; das Chagas et al, 2020 ). Based on information collected from mammalian model systems, the mechanism proposed for this type of inhibition is mediated by Msi1 physically interacting with the Poly(A) binding protein (PABP), both bound to numb mRNA (Kawahara et al, 2008 ).…”
Section: The Musashi Rna Binding Protein Family As Master Regulators Of Neuronal Developmentmentioning
confidence: 99%